Bacteriological study of the portal vein of man - Estefan, Alberto; Parodi, Hernán E.; De Mello, Washington; Juambeltz, Carlos; Pedreira, Walter; Bazet de Brum, Cristina; Christophersen, Inés (Cirugía del Uruguay, 1986)
Prospective bacteriological study of human portal blood in order to determine whether or not there exists a portal flora "normal or physiologicaI". lf the answer is yes, then the study should also provide an answer for the following additional questions: Is it intestina! flora?; The passage of intestinal bacteria into the portal system only occurs when the mucous barrier is altered andlor destroyed? For the bacteriological study a strict paltern was followed in the selection of patients and the bacteriological methodology emoloyed. Three groups of paíients were examined: Group 'A": free trnm biliary pathology 18 cases, Group "B": with acute simple cholangilis. 21 cases: Group "C": with acute septic cholangitis . 8 cases. Results definitively indícate: 1) there exists true portal bacterial flora ; normal o physiological"; 2) bacteria originate at the distal ileurn and especially at the colon; and 3) the passing of intestinal bacteria into the portal system does not necessarily involve an altered and/or destroyed intestinal mucosa.